Preparation and hydrogen penetration performance of TiO2/TiCx composite coatings. (18th May 2020) - Lu, Zhaoxia; Zhou, Qingyun; Ling, Yunhan; Hou, Baorong; Wang, Jipeng; Zhang, Zhengjun
Abstract: Titanium carbide is a good candidate for tritium permeation barrier in a fusion reactor. However, its oxidation susceptibility and the mismatch between the ceramic coating and substrate are still a challenge. In this study, a promising candidate as a hydrogen permeation barrier, comprising a titanium-based ceramic TiO2 /TiCx composite coating, was proposed. The preparation process of this TiO2 /TiCx composite coating involves two steps of carbon ion implantation and oxidation under ultra-low oxygen partial pressure. According to the results, the optimal oxidation temperature for TiO2 coating is 550 °C, with the increase of the oxidation temperature, the particles on the surface of the oxide layer become coarse and loosely arranged, and the protective performance of the oxide layer is greatly reduced. The hydrogen barrier permeation behavior of the composite coating in a fusion reactor was simulated via hydrogen plasma discharge environment, the results show that the hydrogen barrier permeation performance of the composite is significantly better than that of a single TiO2 coating. In addition, the coatings treated with hydrogen plasma showed a certain self-repairing performance through the diffusion growth of the TiCx layer. These findings illustrate a novel method for preparing composite coatings to restrain hydrogen permeation, providing insight into the development of hydrogen permeation barrier materials. Graphical abstract: Image 1 Highlights: A TiO2 /TiCx composite coating was fabricated by C ion implantation. Suitable oxygen potential can passivate TiCx from being over-oxidized. This new coating has excellent hydrogen permeation barrier performance.